2010
DOI: 10.1021/jm900464j
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of 4-Chloro-N-(2-{[5-trifluoromethyl)-2-pyridyl]sulfonyl}ethyl)benzamide (GSK3787), a Selective and Irreversible Peroxisome Proliferator-Activated Receptor δ (PPARδ) Antagonist

Abstract: 4-Chloro-N-(2-{[5-trifluoromethyl)-2-pyridyl]sulfonyl}ethyl)benzamide 3 (GSK3787) was identified as a potent and selective ligand for PPARdelta with good pharmacokinetic properties. A detailed binding study using mass spectral analysis confirmed covalent binding to Cys249 within the PPARdelta binding pocket. Gene expression studies showed that pyridylsulfone 3 antagonized the transcriptional activity of PPARdelta and inhibited basal CPT1a gene transcription. Compound 3 is a PPARdelta antagonist with utility as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 20 publications
2
59
1
Order By: Relevance
“…Preliminary characterization of GSK3787 indicated that this antagonist inhibits both basal and ligand-induced expression of pyruvate dehydrogenase kinase 4 (PDK4) and carnitine palmitoyl transferase 1a (CPT1a) in human skeletal muscle cells at concentrations up to 1 M (Shearer et al, 2010). In addition, this study also demonstrated that oral administration of GSK3787 (10 mg/kg) led to a serum C max of 2.2 Ϯ 0.4 M in C57BL/6 male mice (Shearer et al, 2010).…”
Section: Gsk3787 Antagonizes Ligand-induced Ppar␤/␦-dependent Gene Exmentioning
confidence: 79%
See 4 more Smart Citations
“…Preliminary characterization of GSK3787 indicated that this antagonist inhibits both basal and ligand-induced expression of pyruvate dehydrogenase kinase 4 (PDK4) and carnitine palmitoyl transferase 1a (CPT1a) in human skeletal muscle cells at concentrations up to 1 M (Shearer et al, 2010). In addition, this study also demonstrated that oral administration of GSK3787 (10 mg/kg) led to a serum C max of 2.2 Ϯ 0.4 M in C57BL/6 male mice (Shearer et al, 2010).…”
Section: Gsk3787 Antagonizes Ligand-induced Ppar␤/␦-dependent Gene Exmentioning
confidence: 79%
“…4-[2-(3-Fluoro-4-trifluoromethyl-phenyl)-4-methyl-thiazol-5-ylmethylsulfanyl]-2-methyl-phenoxy}-acetic acid (GW0742) (Sznaidman et al, 2003), GSK0660 (Shearer et al, 2008), and GSK3787 (Shearer et al, 2010) were synthesized by GlaxoSmithKline. Acetic acid, (2-methyl-4-(((4-methyl-2-(4-(trifluoromethyl)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations